Respostas

2013-11-18T00:31:17-02:00
Lembrando que f(x) = y
a) 2x + 5 = 0
2x = 0 - 5
2x = - 5
x = - 5 : 2
x = - 2,5

b) 2x - 1 = 0
2x = 0 + 1
2x = 1
x = 1 : 2
x = 0,5

c) 3x + 1 = 0
3x = 0 - 1
3x = - 1
x = - 1 : 3
x = - 0,333333333... ou - 1/3

d) - 1/2x - 4 = 0
- 1/2x = 0 + 4
- 1/2x = 4
x = 4 : (- 1/2)
x = 4 * (- 2/1)
x = - 8/1
x = - 8

e) - 2x + 3 = 0
- 2x = 0 - 3
- 2x = - 3
x = - 3 : (- 2)
x = 1,5

f) 1/4x + 2 = 0
1/4x = 0 - 2
1/4x = - 2
x = - 2 : 1/4
x = - 2 * 4/1
x = - 8/1
x = - 8

g) 9x + 3 = 0
9x = 0 - 3
9x = - 3
x = - 3 : 9
x = - 0,333333333... ou - 1/3

h) - 1/2x - 1 = 0
- 1/2x = 0 + 1
- 1/2x = 1
x = 1 : (- 1/2)
x = 1 * (- 2/1) 
x = - 2/1
x = - 2

i) - 1/4x + 3 = 0
- 1/4x = 0 - 3
- 1/4x = - 3
x = - 3 : (- 1/4)
x = - 3 * (- 4/1)
x = 12/1
x = 12

j) 6x - 4 = 0
6x = 0 + 4
6x = 4
x = 4 : 6
x = 0,66666666... ou 2/3

Você é ungido de mais :)))))))))))
Amém! Que Deus te abençoe!
http://brainly.com.br/tarefa/211905
responde essa ai pra mim !!